Sistema personalizado de ensino e gamificação: proposta metodológica para programas de treinamento corporativo - Guimarães, Ana Clara Aguiar (2021)
This research aimed to investigate how the Personalized System of Instruction (PSI) (Keller, 1968), combined with game elements, can contribute to the methodological effectiveness of corporate training programs. An internal training on creativity was created with a consulting company in people and business management in Goiânia/GO. It was based on the five main characteristics of PSI: (1) the student's own pace, (2) sequential mastery of the content, (3) classes and demonstrations as motivation channels, (4) emphasis on texts and manuals and (5) monitoring and feedback. It was presented in a hybrid learning environment, with face-to-face meetings and a digital and gamified platform. At the end of the training program, the effectiveness of a gamified PSI adapted and applied to the organizational context was verified, so that there was a 100% utilization of the training program by the participants until the suggested date for completion, resulting, at the organizational level, in a corporate education tool based on scientific principles of Behavior Analysis. Although the data were not conclusive to state that there was operational learning by all participants, it was possible to observe expansions of verbal repertoire, demonstrating evidence of the formation of declarative knowledge